2004
DOI: 10.1309/e4947dg48tvy19c2
|View full text |Cite
|
Sign up to set email alerts
|

Potential Laboratory Misdiagnosis of Hemophilia and von Willebrand Disorder Owing to Cold Activation of Blood Samples for Testing

Abstract: To assess the potential for misdiagnosis of von Willebrand disorder (vWD) and hemophilia A while following current National Committee for Clinical Laboratory Standards (NCCLS) guidelines and consequent to a poorly recognized cold-activation phenomenon, we processed 39 normal citrate-anticoagulated samples by standard procedures (reference) or stored at low (approximately 4 degrees C) or ambient (approximately 22 degrees C) temperature for 3.5 hours before centrifugation and processing. Samples were tested in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(28 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…We demonstrate here that time to centrifugation of blood samples up to 2.5 h does not affect the levels of prothrombin, antithrombin, FVIII, FIX, and FXI. These findings are in accordance with the results of Favaloro et al [8], who reported no effect of time to centrifugation up to 3.5 h, or differences in storage temperature (room temperature vs. cold storage), for measurement of FII, FV, FVII, FIX, FX, FXI, and FXII.…”
Section: Meandifferenceswith95%confidenceintervalswerecalculatedsupporting
confidence: 93%
See 4 more Smart Citations
“…We demonstrate here that time to centrifugation of blood samples up to 2.5 h does not affect the levels of prothrombin, antithrombin, FVIII, FIX, and FXI. These findings are in accordance with the results of Favaloro et al [8], who reported no effect of time to centrifugation up to 3.5 h, or differences in storage temperature (room temperature vs. cold storage), for measurement of FII, FV, FVII, FIX, FX, FXI, and FXII.…”
Section: Meandifferenceswith95%confidenceintervalswerecalculatedsupporting
confidence: 93%
“…The lower level of FVIII in our study after exposure to a cold environment supports the idea that cold activation of FVIII may occur, so levels are less accurate after storage in a cold environment [8,9]. The differences for fibrinogen were too small to be of relevance.…”
Section: Meandifferenceswith95%confidenceintervalswerecalculatedsupporting
confidence: 45%
See 3 more Smart Citations